2021
DOI: 10.1172/jci.insight.147692
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde regulation of mitochondrial genes and FGF21 signaling by hepatic LSD1

Abstract: Mitochondrial biogenesis and function are controlled by anterograde regulatory pathways involving more than one thousand nuclear-encoded proteins. Transcriptional networks controlling the nuclear-encoded mitochondrial genes remain to be fully elucidated. Here we show that histone demethylase LSD1 knockout from adult mouse liver (LSD1-LKO) reduces the expression of onethird of all nuclear-encoded mitochondrial genes and decreases mitochondrial biogenesis and function. LSD1-modulated histone methylation epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Targeting of KDM1A activity has become a promising cancer therapy, and numerous KDM1A inhibitors have been tested in clinical trials ( 40 ). In addition, it has been reported that deficiency of Kdm1a in high-fat diet–fed mice ameliorated NASH and obesity ( 41 ). Our present study supports the KDM1A-SIKE axis as a promising avenue for anti-NASH drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of KDM1A activity has become a promising cancer therapy, and numerous KDM1A inhibitors have been tested in clinical trials ( 40 ). In addition, it has been reported that deficiency of Kdm1a in high-fat diet–fed mice ameliorated NASH and obesity ( 41 ). Our present study supports the KDM1A-SIKE axis as a promising avenue for anti-NASH drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [93] reported that LSD1-modulated histone methylation epigenetically regulates nuclear-encoded mitochondrial genes [93]. Experiments of genome-wide binding and transcriptome analyses demonstrated that LSD1 directly stimulated the expression of genes involved in OXPHOS in cooperation with the nuclear respiratory factor 1 (Nrf1) [94].…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved SWIRM domain of LSD1 interacts with SIRT to form a functional complex, which mediates the activity of SIRT1. The interaction between SIRT1 and LSD1 plays a conserved and cooperative role in H3K4 demethylation to inhibit Notch signalling-mediated gene transcription ( Cao et al, 2021 ). SIRT1 and LSD1 are aberrantly expressed in cancers and play an antagonistic role in DNA repair and mutation acquisition ( Boila and Sengupta, 2020 ; Wang et al, 2020 ).…”
Section: Primary Targets or Signalling Pathways Mediated By Lsd1mentioning
confidence: 99%